Association between oral candidiasis and low CD4+ count among HIV positive patients in Hoima Regional Referral Hospital - Nanteza, Martina; Tusiime, Jayne B.; Kalyango, Joan; Kasangaki, Arabat (BMC Oral Health, 2014)
The aim of this study was to determine the prevalence of Human Immune Virus (HIV) related oral lesions and their association with Cluster of Differentiation 4 (CD4+) count among treatment naïve HIV positive patients. Methods: This was a descriptive and analytical cross sectional study. Participants were 346 treatment naïve HIV positive adult patients. These were consecutively recruited from Hoima Regional Referral hospital between March and April 2012. Data collection involved interviews, oral examinations and laboratory analysis. Results: A total of 168(48.6%) participants had oral lesions. The four commonest lesions were oral candidiasis (24.9%, CI = 20.6-29.7%), melanotic hyperpigmentation (17.3%, CI = 13.7-21.7%), kaposi sarcoma (9.3%, CI = 6.6-12.8%) and Oral Hairy Leukoplakia (OHL) (5.5%, CI = 3.5-8.4%). There was significant association between oral candidiasis and immunosuppression measured as CD4+ less than 350 cells/mm3 (OR = 2.69, CI = 1.608-4.502, p < 0.001). Oral candidiasis was the only oral lesion significantly predictive of immunosuppression (OR = 2.56, CI = 1.52-4.30, p < 0.001) with a Positive Predictive Value (PPV) of 48.2%, Negative Predictive Value (NPV) of 74.3%, 38.1% sensitivity and specificity of 81.4%. Conclusion: Oral candidiasis can be considered as a marker for immunesuppression, making routine oral examinations essential in the management of HIV positive patients.
Keywords: Oral candidiasis; Low CD4+ count; HIV positive patients